Systematic identification and characterization of the soybean (Glycine max) B-box transcription factor family - Chao Sui; Shanshan Cheng; Deying Wang; Lujia Lv; Huiran Meng; Mengxue Du; Jingyu Li; Peisen Su; Shangjing Guo (Biotechnology & Biotechnological Equipment, 2023)
In plants, the B-box (BBX) transcription factors (TFs) are a subfamily of zinc-finger TFs that act to regulate diverse plant growth and development processes. The BBX TFs have been the subject of considerable attention, and are well characterized in diverse plant species, including in rice (Oryza sativa) and Arabidopsis thaliana, but less so in the economically important soybean (Glycine max). In this work, we systematically identified and characterized 57 soybean BBX genes (GmBBX1 to GmBBX57). These genes were mapped to all 20 soybean chromosomes and were divided into five clades with high intra-clade intron–exon similarity. The majority of GmBBX gene promoter cis-acting elements were responsive to light, abscisic acid, salicylic acid and methyl jasmonate, as well as a diverse array of other stimuli. Quantitative RT-PCR indicated that several GmBBX genes exhibited tissue-specific and phytohormone- and abiotic stress-responsiveness. The results of this study will be useful in the continued characterization of soybean BBX gene functions and provide new ideas for soybean breeding.